2013
DOI: 10.1007/s13762-013-0311-3
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of colloid-facilitated contaminant transport in saturated porous media treated by nanoparticles

Abstract: Facilitation of contaminant transport in porous media due to the effect of indigenous colloidal fine materials has been widely observed in laboratory and field studies. It has been explained by the increase in the apparent solubility of low soluble contaminants as a result of their adsorption on the surface of fine particles. Attachment of colloidal fine particles onto the rock surface could be a promising remedy for this challenge. In this experimental study, the effect of five types of metal oxide nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 41 publications
(48 reference statements)
0
25
0
Order By: Relevance
“…For example, they observed that treating the porous medium with silica dispersed in DIW led to approximately 20% reduction in effluent fines concentration as compared to the reference case. They observed that porous media that has been treated with NPs acts as a strong adsorbent of fine particles [9]. Huang et al [30] made a similar observation wherein they observed that for a sand pack treated with NP, the pressure drop across the sand pack was 10% lower than of sand pack without NP, showing an improvement in water injectivity.…”
Section: Unmodified Silica Nanofluidsmentioning
confidence: 91%
See 2 more Smart Citations
“…For example, they observed that treating the porous medium with silica dispersed in DIW led to approximately 20% reduction in effluent fines concentration as compared to the reference case. They observed that porous media that has been treated with NPs acts as a strong adsorbent of fine particles [9]. Huang et al [30] made a similar observation wherein they observed that for a sand pack treated with NP, the pressure drop across the sand pack was 10% lower than of sand pack without NP, showing an improvement in water injectivity.…”
Section: Unmodified Silica Nanofluidsmentioning
confidence: 91%
“…The small size and high specific surface area of NP offer unique advantages like allowing them to easily pass through pore throats and enhanced interaction in the reservoir even with a small quantity of NP. NPs have displayed the potential to act as surface modifiers that could alter the wettability and reduce the oil/water interfacial tension leading to better mobility of the oil phase [1][2][3][4][5][6][7] and reduce fines migration [8,9]. Recent laboratory studies have indicated that nanofluids, which are colloidal dispersions of NP in a dispersing medium have the potential to increase oil recovery [2,7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Arab et al (2014b) investigated the effect of five types of metal oxide NPs, γ-Al 2 O 3 , CuO, MgO, SiO 2 and ZnO, on migrating fines and reported the very enhanced capability of ZnO NP dispersed in distilled water to modify the surface charge of the medium which reduces the repulsive electrostatic forces between a fine and the rock surface which in turn, facilitates particle retention. In addition, Arab and Pourafshary (2013) investigated the effect of NPs to remedy the permeability impairment induced by LSW injection into the Berea sandstone cores.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, application of nanoparticles (NPs) in different fields such as petroleum engineering, [1][2][3][4][5][6][7][8][9][10][11] environmental engineering, and wastewater treatment [12][13][14][15] and chemical engineering [16][17][18] has been considered by many researchers. NPs' applications became widespread as a result of their unprecedented physicochemical properties such as small size (1-100 nm), high specific surface area, very high adsorption potential, and heat conductivity.…”
Section: Introductionmentioning
confidence: 99%